Effects of adding load to the gait of children with cerebral palsy: a three-case report - Camila Rocha Simão; Élida Rayanne Viana Pinheiro Galvão; Débora Oliveira da Silveira Fonseca; Dayse Aleixo Bezerra; Amanda Capistrano de Andrade; Ana Raquel Rodrigues Lindquist (Universidade de São Paulo, 2014)
Our purpose in this study was to analyze the immediate effects of locomotor gait training with different loads on a treadmill on the kinematic parameters of gait in children with Spastic Hemiparetic Cerebral Palsy (SHCP), as well as investigating which load prompted the most adequate motor responses to promote the propulsion of the Paretic Lower Limb (PLL). This case report included 3 children of both sexes, aged 8-12 years. The children walked on the treadmill with loads on their ankles that corresponded to 40, 50 and 60% of the weight of the Lower Limb (LL), on 3 different non-consecutive days. The kinematic parameters were assessed during the pre-training phase (PTPH) and immediately after training (PHI). The spatiotemporal variables did not change immediately after gait training with the aforementioned loads. On the other hand, we observed wider joint angles in the hip and knee during the swing phase immediately after training, especially with a load of 60% of the weight of the lower limb. These findings indicate that the 60% load is the most appropriate to prompt immediate changes in the joint kinematics of the PLL. These alterations can be important in improving propulsion during the swing phase of gait in children with SHCP.